2013
DOI: 10.4028/www.scientific.net/amr.821-822.1189
|View full text |Cite
|
Sign up to set email alerts
|

Sound Insulation Properties of Abandoned Fibers Composites

Abstract: In this article, in order to study the sound insulation properties, abandoned cotton and jute fibers were conducted as reinforced materials, TPU and PP were conducted as matrix materials, and double roller mixing and hot pressing molding processes were adopted to prepare composites. Through the L12 (42×13) mixed orthogonal experiment, cotton/TPU, cotton/PP, jute/TPU and jute/PP composites were prepared respectively. Standing wave tube and impedance tube’s sound absorbing and insulation test system which was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Relation between airflow resistivity and sound absorption of these nonwovens was also established [20]. Studies on using recycled or waste materials are also reported for sound barrier materials [21][22][23][24][25][26][27]. Polyester fibres of different cross-sectional shapes and diameters were used in the nonwoven form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relation between airflow resistivity and sound absorption of these nonwovens was also established [20]. Studies on using recycled or waste materials are also reported for sound barrier materials [21][22][23][24][25][26][27]. Polyester fibres of different cross-sectional shapes and diameters were used in the nonwoven form.…”
Section: Introductionmentioning
confidence: 99%
“…In the reported literature, regarding natural fibre-based composites, it has been confirmed that the selection of fibres [31,32] and matrix [33] using various approaches plays a crucial role in determining the end properties [34,35]. Sound insulation of jute [36], glass, polypropylene, polyester [2], waste fibres [21,23] and inorganic particle [37]-based composites has been investigated by researchers. Particle boards based on coir fibres [3] and agriculture waste such as corn cob [38] have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many researchers make glorious efforts to combine TPU with other materials for a broad application prospect by full exerting the advantages of two materials. , They are focusing on modifying the high-performance fabrics with elastomeric polymers to improve its stab resistance, low-velocity impact and flexural properties and so on. For example, after coating TPU film on aramid fabric reported by Zhang et al, the flexibility of the fabric was decreased slightly, whereas the stab resistance was significantly improved . Neslihan Karaca examined the alternative sound absorption layer, which consisted of three different elastomeric thin submicron fibers web integrated into rigid glass fiber fabric layers .…”
Section: Introductionmentioning
confidence: 99%